Utilisation of neonatologist‐performed echocardiography in shock among neonatologists with interest in haemodynamic: International survey. (21st February 2022) - Meau‐Petit, Virginie; Levy, Yael; Guellec, Isabelle
Abstract: Aim: Neonatologist‐performed echocardiography (NPE) is recommended during shock. We aimed to assess factors associated with NPE utilisation in the NICU and physiological information obtained during management of shock. Methods: An Internet‐based survey, sent to neonatologists with interest in haemodynamics, studying NPE utilisation in shock management through a real clinical case and correlating its use with responders' training and NICU settings. Results: Fifty‐nine completed surveys were received from the United Kingdom: 38%, Western Europe: 32%, Canada: 23% and other countries: 7%. Whilst managing the given clinical case, 90% of responders expected first NPE to exclude congenital heart disease—although only 61% could exclude it confidently (71% in trained clinicians vs. 29% without training; p < 0.01). NPE utilisation prior to initiate treatment was significantly correlated with mean number of neonatologists able to perform NPE in the NICU (4.9 vs. 2.9 neonatologists per unit; p = 0.02). Similarly, for ongoing therapeutic guidance, NPE was more used in trained clinicians ( p < 0.01). 88% and 81% of responders studied a combination of multiple parameters to assess filling and systemic flow, respectively. Conclusion: Neonatologist‐performed echocardiography during shock management differs with previous training and number of doctors able to perform echocardiography in NICU. This study highlighted the need for enhanced training implementation.